КОНЦЕПТ «ТОЛЕРАНТНОСТЬ» В РУССКОЯЗЫЧНОЙ ЗАРУБЕЖНОЙ ПРЕССЕ СЛАВЯНСКИХ ГОСУДАРСТВ - Жданова, Ирина (Acta Neophilologica, 2016)
This article examines the nominative field of the concept “tolerance” on the basis of material collected from the Russian-language foreign press of Slavic States media texts. The analysis of the nominative field is carried out from the perspective of a semanticcognitive approach towards the correlation between semantic and cognitive processes. The research of the semantics of language units of the nominative field objectifying this concept allows the author to represent the content of the concept “tolerance” in the form that it is reflected and recorded in the Russian-language foreign press media texts